Black Children Matter - Wright, Mia (My University, 2025)
Racial disproportionality is defined as a condition that exists when the proportion of one group in the child welfare population is proportionately larger (overrepresented) or smaller (underrepresented) than the proportion of the same group in the general child population (Detlaff & Boyd, 2020). Being Black is part of my identity and something I take pride in. It is no secret that historically Black people have experienced disproportionality, assimilation, and racism. As I have grown through my social work journey, I have realized my passion is children and preparing them to lead the future generations. All children deserve the right to safety, well-being, and permanency. Throughout history, racism against Black people has been prevalent at every level. In child welfare, Black children are disproportionately represented.
Master of Social Work (MSW)
Keywords: anti-racist; child welfare; disproportionality; systemic racism